MAN AND HIS ARTISTIC WORLD IN ABDULLA ARIPOV'S POETRY - Raykhonova Mukhayyo Muhammadievna (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This article analyzes the artistic criteria of Abdulla Aripov's work and his unique poetry in our literature. Abdulla Aripov's individual style, the system of images he created, reflected the process of expressing the reality of a talented poet, the delicate human feelings in his heart, in a unique way, which is relevant to man and the world. It is commented that the poet sang in modern Uzbek poetry the complexity, contradictions, injustices, justice, depravity of the human heart in a deep and truthful, especially unique way.